Proses Kreativitas Aransemen Lagu Lir-Ilir Oleh Grup Musik Rungon Wresthi - Irfanda Rizki Harmono Sejati; Ghazian Arka Fikry (Program Studi Pendidikan Musik FBS UNP, 2022)
Creativity is a thought or idea that exists in a person to create new things that have never been thought of by others, including in terms of arrangement. In the arrangement there is a process of creation, because the music to be arranged is the basic material, while the music that has been arranged must contain overall plus values ​​both in chords, melodies, accompaniment patterns, fillers and counter melodies. Rungon Wresthi is one of the music groups located in the city of Semarang. This musical group has its own uniqueness and charm in presenting its musical creativity. This study uses a qualitative research method with descriptive exposure, with the aim of revealing the creative method and background of the Rungon Wresthi music group in composing songs. The results of this study can be seen from the four elements of creativity from Rhodes' theory which show how Rungon Wresthi has creativity in creating works which in this context are in the form of Lir-Ilir song arrangements.